The impact of Covid 19 on the sinuses, with a logistical assessment to know the risk factors. (Texas Journal of Medical Science, 2023)
Sinusitis is the inflammation of the paranasal sinuses; these are cavities that we have in the face, as well as in the head, around the nose, and inside it. When such inflammation occurs, and this affects the nasal passages.